PENGARUH ASAS KERAHASIAAN DATA DAN INFORMASI WAJIB PAJAK PADA PENGAMPUNAN PAJAK (TAX AMNESTY) TERHADAP PENEGAK HUKUM DI INDONESIA - Damayanti, Ratih (Department of Constitutional and Administrative Law, Faculty of Law Universitas Negeri Semarang (UNNES)., 2019)
The purpose of this article is to find out the implementation and issues of confidentiality principle in Act No. 11 of 2016 concerning Tax Amnesty and to determine the effect of the principle of confidentiality of data and information on taxpayers in Act No 11 of 2016 concerning Tax Amnesty for law enforcement in Indonesia. The principle of confidentiality in Tax Amnesty provides a potential moral hazard. A moral hazard occurs because of the opportunities that enable these actions to materialize. Opportunities for Fiscus and Taxpayers to meet in person. This has the potential to cause a gray area between the Taxpayer and the Fiscus which can cause a moral hazard to the Taxpayer. The authority of the Fiscus is prone to be misused so that it can lead to several criminal actions that can be carried out, namely embezzlement or corruption that can harm the country's finances. When the crime occurs at a Tax Amnesty Taxpayer, it will be difficult to enforce the law because the data and information sourced from the Statement and the attachments that are administered cannot be used as a basis for investigation, investigation, and/or criminal prosecution of the Taxpayer cannot be used as a basic investigation, investigation and/or criminal prosecution of taxpayers.